STRENGTHENING THE ABILITY TO READ THE QUR'AN THROUGH THE IMPLEMENTATION OF THE UMMI METHOD WITH THE ASSET BASED COMMUNITY DEVELOPMENT (ABCD) APPROACH AT THE AT-TAQWA TPA IN JORONG BAMBAN SARASOK - Zoni Leo Nardo; Nana Sepriyanti; Martin Kustati (CV. Naskah Aceh, 2026)
This research is motivated by the challenges in improving the ability to read the Qur'an for students at TPA At-Taqwa, especially in the aspects of tajwid, fluency , and understanding of the text . This study aims to analyze the effectiveness of the application of the UMMI method through the Asset Based Community Development (ABCD) approach in strengthening the ability to read the Qur'an. The ABCD approach is used by emphasizing the utilization of local potential and the active involvement of participants in the learning process . The research method used is a descriptive approach with a participatory design through training , mentoring , and evaluation activities . The results of the study indicate that the systematic and structured application of the UMMI method is able to significantly improve the ability to read the Qur'an of students , which is shown through increased mastery of tajwid, reading fluency , and understanding of the Qur'an text . In addition , participant feedback shows a positive response to the applied learning model . Thus , UMMI method training based on the ABCD approach is proven to be effective in improving the quality of Qur'an learning . This study confirms that the involvement of Active participation of participants and utilization of community assets are key factors in achieving optimal learning outcomes.